Implementasi Pendidikan Akhlak dalam Pembentukan Akhlak Keseharian Santri - Izzah, Lathifatul; Hanip, Muhammad (Universitas Alma Ata, 2018)
This paper aims to determine the source of teaching and learning materials of moral in the formation of morals daily santri, explain the implementation of moral education, and want to know the supporting factors and inhibiting the implementation of moral education in the formation of the morals daily santri. With that goal, got point point about moral character formation in moral education, among which is the source of moral education in the discourse of moral students taken from some classic books, namely Taisirul Kholak, Taklim Muta'alim, Akhlak Lilbanin 4 Juz, Bidayatul Bidayah and some other books of morality tasawuf. Learning materials related to morphology are taken from Taisirul Kholak, Bidayatul Hidayah and Akhlak Lilbanin. Related to the little wash of material taken from Taisir, Bidayah and some related Fiqh books to wash, as well as so on until morals towards the environment. Some methods are quite effective in the moral education of santri in moral education is through habituation, exemplary, discipline, and sometimes reward and punishment. Factors supporting the formation of santri morality is a religious learning activity, adequate facilities, the spirit of ustad / ustadzah and santri, comfortable environment and away from the crowd, there are disciplines that must be obeyed santri. Apart from the supporting factors there are inhibiting factors, namely the presence of violations of students and the inï¬‚ uence of outside the cottage.Keyword: the consept of moral education, method, resources and teaching materials, theformation of santri morality